A curcumin activated carboxymethyl cellulose–montmorillonite clay nanocomposite having enhanced curcumin release in aqueous media. (10th December 2015) - Madusanka, Nadeesh; de Silva, K.M. Nalin; Amaratunga, Gehan
Highlights: A novel curcumin activated MMT–CMC nanocomposite was prepared. CMC was used as an emulsifier for curcumin. MMT nanoclay acts as a matrix material while playing a role in release kinetics. Solubility of curcumin in the nanocomposite increased in the aqueous medium. Abstract: A novel curcumin activated carboxymethylcellulose–montmorillonite nanocomposite is reported. A superabsorbent biopolymer; carboxymethyl cellulose (CMC) was used as an emulsifier for curcuminwhich is a turmeric derived water insoluble polyphenolic compound with antibacterial/anti-cancer properties. Montmorillonite (MMT) nanoclay was incorporated in the formulation as a matrix material which also plays a role in release kinetics. It was observed that water solubility of curcumin in the nanocomposite has significantly increased (60% release within 2 h and 30 min in distilled water at pH 5.4) compared to pure curcumin. The prepared curcumin activated carboxymethylcellulose–montmorillonite nanocomposite is suitable as a curcumin carrier having enhanced release and structural properties.